2016
DOI: 10.1016/j.tsc.2015.10.009
|View full text |Cite
|
Sign up to set email alerts
|

Beyond belief: Structured techniques prove more effective than a placebo intervention in a problem construction task

Abstract: Problem construction is one of the first steps in creative problem solving and research has shown clear links between problem construction ability and creative output. Here, we compared two active techniques with that of a placebo intervention and show a benefit in problem construction performance for the active techniques. The active techniques required participants to either utilise six questions (six men), or adopt six perspectives, incorporating a range of specific questions (six hats). The placebo interve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 34 publications
(44 reference statements)
2
3
0
Order By: Relevance
“…Therefore, hypothesis 2 was confirmed. This result is in line with the study of Vernon and Hocking (2016).…”
Section: Discussionsupporting
confidence: 93%
“…Therefore, hypothesis 2 was confirmed. This result is in line with the study of Vernon and Hocking (2016).…”
Section: Discussionsupporting
confidence: 93%
“…The authors found that those who were instructed to make restatement of a marketing campaign problem produced more creative ideas than those who were not instructed. A similar finding of active engagement in problem construction through structured activities was observed in later work (e.g., Vernon & Hocking, 2014, 2016). Instructions can also be beneficial for team problem construction.…”
Section: Meeting Influencessupporting
confidence: 83%
“…Use of the STH in a problem construction task, involving restating a given problem, has been shown to increase the number of restatements, with such restatements being classified as more original compared with the responses from a no-intervention control group (Vernon & Hocking, 2014, 2016). This shows that helping to structure the problem finding process in this way can improve an individual’s creative output.…”
Section: Methodsmentioning
confidence: 99%
“…Such a view is consistent with research showing that the use of open questions elicits more diverse responses than close-ended questions (e.g., Reja, Manfreda, Hlebec, & Vehovar, 2003). Vernon and Hocking (2014) showed that participants who used this tool in a problem construction task, which required them to restate a given problem, produced a greater number of ideas that were rated as more original compared with a no-intervention control group (see also Vernon & Hocking, 2016). The use of such open-ended questions can encourage the individual to stretch themselves and adopt multiple perspectives when dealing with a problem, which some have argued would support the later problem solving processes (McFadzean, 1998).…”
Section: Problem Finding Toolsmentioning
confidence: 99%